Development of ELCOCS Learning Media to Improve Collaboration Skills and Learning Outcomes of Junior High School Students - Azmi, Difa’; Mulyati, Yayuk; Danissa, Fanny; Hasan, Said; Wicaksono, Azizul (Indonesian Journal of Biology Education, 2024)
Facing the era of Society 5.0, competence and adaptation are important aspects in education. The transition from Industrial Revolution 4.0 to Society 5.0 demands 21st century skills, with a focus on 4C skills (Communication, Collaboration, Critical Thinking and Problem Solving, and Inventiveness and Innovation), needs to be integrated in the teaching and learning process. But in reality, collaboration skills and student learning outcomes are still low, especially in the circulatory system material which is considered difficult. This research aims to develop Enjoyable Learning-based learning media, which is expected to improve collaboration skills and student learning outcomes. The method used was R&D with the ADDIE model which involved analysis, design, development, implementation, and evaluation. The subjects of this research were 44 8th grade students and 2 junior high school science teachers at SMP Nasional Malang. The results of validation by experts showed that ELCOCS (Enjoyable Learning for Collaboration Skills on Circulatory System) media has a very valid category with a media validity percentage of 84.4% and material validity of 87.91%. The practicality test by teachers and students also showed a very practical category with a percentage of teacher practicality of 94.4% and student practicality of 87.65%. The excellent results from the validity and practicality tests indicate that this media is not only suitable for use but also has the potential to improve collaborative skills and student learning outcomes.